Weight estimation accuracy of certificated garut ewes by using novel formula, schoorl formula, and winter arjodarmoko formula - Harsa, Jois; Heriyadi, Denie; Ramdani, Diky (Faculty of Animal Science, Universitas Brawijaya, 2020)
The body weight (BW, in kg) of sheep can be estimated by measuring the body length (BL, in cm) and chest circumference (CC, in cm). The study aimed to conduct anovel formula to predict BW of Garut ewesbased onits BL and Chest Circumference CC. The accuracy of the novel formula is then comparedto the commonly used Schrool and Winter Arjodarmoko formulas. The materials of the study weretaken from the1 to 7 certified data of adult Garut ewes with a total of 118 heads from three different regions: Bandung (73 ewes), Sumedang (22 ewes) and Garut (23 ewes). The observed variables were Body Weight (BW), Body Length(BL), and Chest Circumference (CC). The data showed that the average adultGarut ewesBW was at 44.05 ± 10.65 kg, BL at 62.35 ± 5.34 kg, and CCat 83.89 ± 6.25 kg. The novel formularegressionanalaysis for BW estimationwas (-91.1+ 0.575 (BL) + 1.18 (CC) with R2 = 81.0%. Moreover, BL and CC showed highly significant correlation (P<0,001) with the BW. The novel formula calculation showed the averageBW was 42.74 kg (-0.32 kg deviation), while the Schrool formula showed the average BW was 44.47 kg (+0.42 kg deviation), and Winter Arjodarmoko was 44.48 kg (+0.43 kg deviation). The reseach concludes that the novel formula for Garut ewesBW estimation had the smallest deviation compared to Schoorl and Winter Arjodarmoko formulas.